Using auditory pre-information to solve the cocktail-party problem: electrophysiological evidence for age-specific differences - Getzmann, Stephan; Lewald, Jörg; Falkenstein, Michael (Frontiers in Neuroscience, 2014)
Speech understanding in complex and dynamic listening environments requires (a) auditory scene analysis, namely auditory object formation and segregation, and (b) allocation of the attentional focus to the talker of interest. There is evidence that pre-information is actively used to facilitate these two aspects of the so-called “cocktail-party“ problem. Here, a simulated multi-talker scenario was combined with electroencephalography to study scene analysis and allocation of attention in young and middle-aged adults. Sequences of short words (combinations of brief company names and stock-price values) from four talkers at different locations were simultaneously presented, and the detection of target names and the discrimination between critical target values were assessed. Immediately prior to speech sequences, auditory pre-information was provided via cues that either prepared auditory scene analysis or attentional focusing, or non-specific pre-information was given. While performance was generally better in younger than older participants, both age groups benefited from auditory pre-information. The analysis of the cue-related event-related potentials revealed age-specific differences in the use of pre-cues: Younger adults showed a pronounced N2 component, suggesting early inhibition of concurrent speech stimuli; older adults exhibited a stronger late P3 component, suggesting increased resource allocation to process the pre-information. In sum, the results argue for an age-specific utilization of auditory pre-information to improve listening in complex dynamic auditory environments.